How Is Endoscopic Submucosal Dissection for Gastrointestinal Lesions Being Implemented? Results from an International Survey - Araújo-Martins, Miguel (GE Port J Gastroenterol, 2020)
BACKGROUND AND STUDY AIM: Superficial gastrointestinal (GI) neoplasms can be treated with endoscopic mucosal resection (EMR) and/or endoscopic submucosal dissection (ESD). These techniques are widely used in Eastern countries; however, its use in the West is limited. The aim of this study was to evaluate the current implementation of ESD in Western countries. METHODS: Western endoscopists (n = 279) who published papers related to EMR/ESD between 2005 and 2017 were asked to complete an online survey from December 2017 to February 2018. RESULTS: A total of 58 endoscopists (21%) completed the survey. Thirty performed ESD in the esophagus (52%), 45 in the stomach (78%), 36 in the colorectum (62%), and 6 in the duodenum (10%). The median total number of lesions ever treated per endoscopist was 190, with a median number per endoscopist in 2016 of 41 (7 [IQR 1–21], 6 [IQR 4–16], and 28 [5–63] in the esophagus, in the stomach, and in the colon and rectum, respectively). En bloc resection rates were 97% in the esophagus, 95% in the stomach, and 84% in the colorectum. Complete resection (R0) was achieved in 88, 91, and 81%, respectively. Curative rates were 69, 70, and 67%, respectively. Major complications (perforation or delayed bleeding) occurred more often in colorectal ESD (12 vs. 6% in the esophagus and 7% in the stomach). In the upper GI tract, the majority of resected lesions were intramucosal adenocarcinoma (59% in the esophagus; 47% in the stomach), while in the colorectum the majority were adenomas (59%). CONCLUSION: ESD seems to be performed by a large number of centers and endoscopists. Our results suggest that ESD is being successfully implemented in Western countries, achieving a good rate of efficacy and safety according to European guidelines.